Microdevice for aqueous humor drainage Maldonado Bas - Pförtner - Maldonado-Bas,Arturo (2011)
PURPOSE: A microdevice for the treatment of refractory glaucoma is presented. The underlying concepts, its mechanisms of action and the surgical technique for implanting are explained and the results are analyzed. The microdevice was developed and the surgeries were performed at the Maldonado-Bas Eye Clinic (Cordoba, Argentina), under the rules established in the protocol approved by the provisions of the National Administration of Drugs, Food and Medical Technology 430/7. File No.:1-47-25-649-07-1. METHODS: In a prospective study, following the protocol, 16 eyes with refractory glaucoma were included and operated. Intraocular pressure <21mmHg with or without additional medication was considered successful. The follow-up was one year. Averages, percentages and their 95% confidence bands were calculated. Analysis of variance for repeated measures was used to compare averages. RESULTS: The average preoperative intraocular pressure was 32.81 mmHg, SD ± 10.94 mmHg in a range of 14 to 50 mmHg. The average post-surgical intraocular pressure at one year was 12.43 mmHg, SD ± 2.85 mmHg in a range of 7 to 19 mmHg. The difference between the pre-and post-surgery average intraocular pressure was 20.38 mmHg. The number of successes was 14 eyes (87.5%, confidence interval (CI) 95% 61.6% - 98.6%). The number of failures was two eyes (12.5%, CI 95% 1.43% - 38.4%). CONCLUSIONS: The results show that the microdevice is successful for the treatment of refractory glaucoma.